Dynamics of Public Communication in the Bangkonol Landfill Conflict, Pandeglang - Sutisna, Nana; Sjuchro, Dian Wardiana; Priana, Ronny Yudhi Septa; Fitriana, Rina (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
The conflict over the Bangkonol Landfill (TPA Bangkonol) in Pandeglang Regency, Banten Province, escalated during 2024–2025, involving local government, communities, and the media. This study analyzes the dynamics of public communication by focusing on community resistance, media framing, and the government’s crisis response. A qualitative case study was conducted through interviews, document analysis, and media review. Findings indicate that the absence of participatory communication triggered strong community resistance, while the media amplified the dispute by framing it as an environmental crisis and highlighting weak policy legitimacy. These dynamics align with agenda-setting and framing theories, which explain how media influence public opinion. The issue was further politicized by local political rivals, and digital platforms became arenas for mobilization, consistent with uses and gratifications theory. This shows that communication failure not only fueled resistance but also opened space for politicization and accelerated conflict escalation. The study recommends strengthening official communication channels, ensuring community involvement from the planning stage, and expediting the transition of the landfill to a sanitary system.